A Qualitative Description of Direct Care Workers of Lesbian, Gay, Bisexual, Transgender Older Adults. (April 2023) - May, Jennifer T.; Rainbow, Jessica G.
Purpose: The aim of the study was to examine direct care worker (DCW) perceptions of lesbian, gay, bisexual, transgender (LGBT) older adults living in long-term care, assisted living, and home health settings. DCWs provide the closest interaction with LGBT older adults in these settings. The perceptions DCWs have toward LGBT older adults is important because the quality of care can be influenced by negative attitudes.Methodology: Qualitative description was used to synthesize what is known about DCWs' perceptions toward LGBT older adults.Results: The overarching theme, "Care is Different, but Not my Care, " was supported by the categories Cues of Stereotyping, Cues of Prejudice, and DCWs' Social System and Reported Care.Application: Specific implications for practice (i.e., training, recruitment, retention strategies) and policy (i.e., mandated staffing ratios, pay) are explicated to guide future interventions to ensure equitable, quality care in health care.